Ukuran KAP, Audit Tenure, Pergantian Auditor, Komite Audit, Listing Age, Dan Audit Report Lag - Radina Modjaningrat; Syaiful Bahri (Journal of Innovative and Creativity, 2025)
The study aims to analyze the influence of audit firm size, audit tenure, auditor turnover, audit committee, and listing age on audit report lag. The study examined coal mining companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. Audit firm size, audit tenure, and audit committee negatively affected audit report lag (ARL). Larger audit firms have more auditors, better trained staff, and more sophisticated audit technology, enabling faster and more efficient audit completion. Auditors with a long track record of dealing with clients have a better understanding of the company's characteristics, systems, and risks, enabling faster and more efficient audit processes. The existence and effectiveness of an audit committee accelerates audit completion. Auditor turnover and listing age do not affect ARL. The audit process is not significantly affected by the appointment of a new auditor, as it must comply with Public Accounting Professional Standards (SPAP). Older listed companies do not always complete audits faster than newer ones.